Glucose Responsiveness of β-Cells Depends on Fatty Acids - Gerst, Felicia; Singer, Christine; Noack, Katja; Graf, Dunia; Kaiser, Gabriele; Panse, Madhura; Kovarova, Marketa; Schleicher, Erwin; Häring, Hans-Ulrich; Drews, Gisela; Ullrich, Susanne (Experimental and Clinical Endocrinology & Diabetes, 2019)
Glucose-stimulated insulin secretion (GSIS) is the gold standard for β-cell function. Both experimental and clinical diabetology, i. e., preceding transplantation of isolated human islets, depend on functional testing. However, multiple factors influence GSIS rendering the comparison of different in vitro tests of glucose responsiveness difficult. This study examined the influence of bovine serum albumin (BSA)-coupled fatty acids on GSIS. Isolated islet preparations of human donors and of 12-months old mice displayed impaired GSIS in the presence of 0.5% FFA-free BSA compared to 0.5% BSA (fraction V, not deprived from fatty acids). In aged INS-1E cells, i. e. at a high passage number, GSIS became highly sensitive to FFA-free BSA. Readdition of 30 µM palmitate or 30 µM oleate to FFA-free BSA did not rescue GSIS, while the addition of 100 µM palmitate and the raise of extracellular Ca2+from 1.3 to 2.6 mM improved glucose responsiveness. A high concentration of palmitate (600 µM), which fully activates FFA1, largely restored insulin secretion. The FFA1-agonist TUG-469 also increased insulin secretion but to a lesser extent than palmitate. Glucose- and TUG-induced Ca2+oscillations were impaired in glucose-unresponsive, i. e., aged INS-1E cells. These results suggest that fatty acid deprivation (FFA-free BSA) impairs GSIS mainly through an effect on Ca2+sensitivity.
Keywords: insulin secretion; fatty acids; albumin; glucose responsiveness